Hydrophobicity Properties of Silica-Dimethylsilicone Oil-Stearic Acid Based Materials Applied as Waterproof Coating Materials - Joko Suryadi; Annisa Sri Rahmawati; Derina Maulinda; Ndaru Dwiyatmoko Mukti; Andhika Putera Utama; Haryadi (KOVALEN: Jurnal Riset Kimia, 2026)
Geothermal solid waste is one of the byproduct materials from the geothermal energy process. The silica extracted from this solid waste can be utilized as a raw material for waterproof coatings. The waterproof or hydrophobic properties in this study have been studied with a formulation of silica, stearic acid, and dimethyl silicone oil. The technique of extracting silica from geothermal waste is carried out using the sol-gel method. Preparation of hydrophobic materials is carried out by mixing silica with stearic acid at a ratio of 1:3, 1:5, and 1:7 on a mass basis with the addition of dimethyl silicone oil as an emulsifier. The hydrophobic silica-dimethyl silicone oil-stearic acid materials were synthesized and characterized by functional group analysis using FTIR. The best hydrophobic properties are shown in a ratio of silica and stearic acid of 1:5. On a glass substrate, the silica-dimethyl silicone oil-stearic acid coating produced a contact angle of 110.2 °. On a fabric substrate, the coating exhibited a superhydrophobic phenomenon with a contact angle of 153.7 °.